NiCo2O4/g‐C3N4 Heterojunction Photocatalyst for Efficient H2 Generation. Issue 5 (20th March 2021) - Fan, Yanyun; Chen, Hongmei; Cui, Danfeng; Fan, Zheng; Xue, Chenyang
Abstract : Herein, a novel NiCo2 O4 /g‐C3 N4 heterojunction photocatalyst is synthesized, which shows excellent photocatalytic activity. Photocatalysis studies reveal that the hydrogen generation rate of the 5%‐NiCo2 O4 /g‐C3 N4 composite photocatalyst can reach 1041.9 μmol g −1 h −1 . NiCo2 O4 and g‐C3 N4 form a heterojunction, which enhances the absorption capacity of visible light, promotes the separation of charges, and inhibits the recombination of carriers, consequently, improving the performance of photocatalytic hydrogen generation. The photocatalytic reaction mechanism of the NiCo2 O4 /g‐C3 N4 heterojunction composite is discussed, which provides a method for studying bimetal oxide‐based photocatalysts. Abstract : A novel 5%‐NiCo2 O4 /g‐C3 N4 heterojunction photocatalyst shows excellent photocatalytic activity, and the hydrogen generation rate can reach 1041.9 μmol g −1 h −1 . NiCo2 O4 and g‐C3 N4 form a heterojunction, which promotes the separation of charges and inhibits the recombination of carriers, consequently, improving the performance of photocatalytic hydrogen generation. Furthermore, the possible reaction mechanism of the NiCo2 O4 /g‐C3 N4 heterojunction composite is discussed.